Extending the use of Spanish Computer-Assisted Anomia Rehabilitation Program (CARP-2) in people with Aphasia. - Adrián-Torres, José Antonio; González-Sánchez, Mercedes; Buiza-Navarrete, Juan José; Sage, Karen Eleonor (Elsevier, 2011)
Purpose: To extend the use of the Spanish Computer-assisted Anomia Rehabilitation Program (CARP-2) for anomia from a single case to a group of 15 people with aphasia. To evaluate whether the treatment is active (Phase 1) for this group (Robey & Schultz, 1998), providing potential explanations as to why. Methods: Fifteen participants with chronic aphasia (with a range from moderate to mild anomia) were recruited to 15 weeks of computer-assisted therapy for anomia. A single treatment period with pre- and post-treatment assessments evaluated participants’ ability to name 200 words using the multiple cues provided by the computer. Pre- and post-naming measures of all items examined the effect of treatment. Background linguistic and cognitive skills were measured before and after the therapy to investigate whether the improvements in naming were therapy specific. Results: All 15 participants showed significant benefits in their naming skills after the therapy. There were no changes to cognitive and linguistic skills unrelated to anomia. There was evidence of some carry-over effects in naming. Conclusion: The Spanish Computer-assisted Anomia Rehabilitation Program (CARP-2) for anomia is an active treatment for a range of people who have anomia as part of their aphasia profile.
https://openpolicyfinder.jisc.ac.uk/id/publication/13827
Keywords: Afasia - Innovaciones tecnológicas; Tecnología de la rehabilitación; Anomia; Aphasia; Computer assisted rehabilitation